2016
DOI: 10.1155/2016/4145708
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-Beta Induced Changes in Vesicular Transport of BDNF in Hippocampal Neurons

Abstract: The neurotrophin brain derived neurotrophic factor (BDNF) is an important growth factor in the CNS. Deficits in transport of this secretory protein could underlie neurodegenerative diseases. Investigation of disease-related changes in BDNF transport might provide insights into the cellular mechanism underlying, for example, Alzheimer's disease (AD). To analyze the role of BDNF transport in AD, live cell imaging of fluorescently labeled BDNF was performed in hippocampal neurons of different AD model systems. BD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 94 publications
(118 reference statements)
2
13
0
Order By: Relevance
“…It remains to be determined to what extent and at what time the exposure to various peptides affects mitochondrial ROS production or calcium buffering in respect to changes in axonal trafficking. Our data are consistent with recently reported observations that anterograde and retrograde transport of brain-derived neurotrophic factor (BDNF) - containing vesicles but not the activity-dependent release of BDNF from these vesicles was affected after the acute treatment with Aβ42 peptides in neurons (Seifert et al, 2016). Indeed, we have shown that partial inhibition of mitochondrial complex I with small molecules induces a positive metabolic adaptation resulting in a reduction of pTau and Aβ levels, and the activity of GSK3β in multiple mouse models of AD (Zhang et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…It remains to be determined to what extent and at what time the exposure to various peptides affects mitochondrial ROS production or calcium buffering in respect to changes in axonal trafficking. Our data are consistent with recently reported observations that anterograde and retrograde transport of brain-derived neurotrophic factor (BDNF) - containing vesicles but not the activity-dependent release of BDNF from these vesicles was affected after the acute treatment with Aβ42 peptides in neurons (Seifert et al, 2016). Indeed, we have shown that partial inhibition of mitochondrial complex I with small molecules induces a positive metabolic adaptation resulting in a reduction of pTau and Aβ levels, and the activity of GSK3β in multiple mouse models of AD (Zhang et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Lower levels of BDNF correlate with poor cognitive status and higher amyloid‐beta protein (Beeri & Sonnen, ; Buchman et al ., ). Soluble Aβ oligomers impair both vesicular and axonal BDNF trafficking resulting in disruption of BDNF signaling, which underlies the synaptic dysfunction displayed in AD (Poon et al ., ; Seifert et al ., ). BDNF plays a critical role in the formation and survival of neurons, maintenance of structural and functional plasticity and is a key player of plasticity and memory (Korte et al ., ; Rex et al ., ; Park & Poo, ).…”
Section: Discussionmentioning
confidence: 97%
“…Seifert and colleagues also reported impairments in both the anterograde and retrograde transport of BDNF-containing vesicles in hippocampal neurons derived from another AD mouse model (5xFAD) with increased Aβ expression. In the study, a fast action (within 5 min) of Aβ on the transport was also revealed [ 168 ]. Gan et al proposed Ca 2+ -dependent mechanisms of the disruption of BDNF transport induced by Aβ oligomers.…”
Section: Bdnf/trkb Transport As a Therapeutic Target Of Neurodegementioning
confidence: 99%